The demand for alcohol in ireland - Thom, Dr (Economic & Social Studies, 1984)
Abstract: Equilibrium and dynamic versions of Deaton and Muellbauer's AID S model are used to estimate demand systems for Irish consumption of beer, spirits and wine using quarterly data for the period 1969-1980. The dynamic model is preferred on the grounds that it allows both homogeneity and symmetry whereas the equilibrium model does not. Estimated elasticities are used to derive tax elasticities for the change in revenue resulting from changes in excise duties. These elasticities are unambiguously positive.
Keywords: Economics; Sociology